ACCOUNTING INFORMATION SYSTEMS AND FINANCIAL PERFORMANCE OF MICRO FINANCE INSTITUTIONS IN MERU COUNTY - Mukembu, Morris Mwenda (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Accounting Information System is one of the important technologies in any financial or non-financial institution operations. AIS are used in capturing, processing, storing and distributing accounting information. In implementing financial internal control system, the role of AIS is critical. The study aimed at providing an understanding of influence of AIS on microfinance institutions financial performance in Meru County, Kenya. The objective identified for the study was; to determine the influence of information quality on financial performance of micro finance institution in Meru County, Kenya. The study was guided by adverse selection theory; employed descriptive research design had target population of 316 with a sample size of 177 respondents. Structured closed and open ended questionnaire was the main data collection tool. Data was analyzed by the use of SPSS version 28. Data was analyzed by use of descriptive statistics, Pearson’s correlation, ANOVA and multiple linear regressions. A pilot test was carried to ensure validity and reliability. The variable was tested for reliability by use of Cronbach alpha coefficient attaining 0.862. The regression was tested at 5% level of significant. The results had a mean of 1.63 with SD of 0.621 on a 5-point Likert scale starting with 1- strongly agree to 5- strongly disagree. Pearson’s correlation coefficient was 0.218 at α =.001 which is less than .05 level of significance. Regression analysis beta coefficient for the independent variable is β = .501 at p < .05 level of significant. The results indicate that the variable is statistically significant. Null hypothesis was tested using F – test (2.388) at 95% confidence level and the results lead to the rejection of the null hypothesis. The study concluded that financial performance of MFIs in Meru County has increased moderately. Thus, there is need to adopt AIS in order to improve in financial performance. Keywords: Accounting Information System, Financial Performance, Financial Institutions